Technique failure in peritoneal dialysis: Modifiable causes and patient-specific risk factors - Anna A Bonenkamp; Anita van Eck van der Sluijs; Friedo W Dekker; Dirk G Struijk; Carola WH de Fijter; Yolande M Vermeeren; Frans J van Ittersum; Marianne C Verhaar; Brigit C van Jaarsveld; Alferso C Abrahams (SAGE Journals, 2023)
Background:
Technique survival is a core outcome for peritoneal dialysis (PD), according to Standardized Outcomes in Nephrology-Peritoneal Dialysis. This study aimed to identify modifiable causes and risk factors of technique failure in a large Dutch cohort using standardised definitions.
Methods:
Patients who participated in the retrospective Dutch nOcturnal and hoME dialysis Study To Improve Clinical Outcomes cohort study and started PD between 2012 and 2016 were included and followed until 1 January 2017. The primary outcome was technique failure, defined as transfer to in-centre haemodialysis for ≥ 30 days or death. Death-censored technique failure was analysed as secondary outcome. Cox regression models and competing risk models were used to assess the association between potential risk factors and technique failure.
Results:
A total of 695 patients were included, of whom 318 experienced technique failure during follow-up. Technique failure rate in the first year was 29%, while the death-censored technique failure rate was 23%. Infections were the most common modifiable cause for technique failure, accounting for 20% of all causes during the entire follow-up. Leakage and catheter problems were important causes within the first 6 months of PD treatment (both accounting for 15%). APD use was associated with a lower risk of technique failure (hazard ratio 0.66, 95% confidence interval 0.53–0.83).
Conclusion:
Infections, leakage and catheter problems were important modifiable causes for technique failure. As the first-year death-censored technique failure rate remains high, future studies should focus on infection prevention and catheter access to improve technique survival.
Keywords: Medicine